Non-timber forest products’ marketing in Nigeria. A case study of Osun state (2006)
Research on markets and marketing of some non-timber forest products (NTFPs) was carried out in selected locations of Osun State. The NTFPs considered are chewing sticks such as Massularia acuminata and bush meat like Thryonomys swinderianus, representing both the flora and fauna aspects of NTFPs, respectively. Five Local Government Areas were randomly selected, namely; Odo-otin, Boripe, Iwo, Irewole and Atakunmosa for the research purpose. A total of 300 questionnaires were administered, 150 questionnaires for each of the NTFPs. Each NTFPs was further subdivided to production, marketing and usage or consumption with 50 questionnaires for each unit. It was gathered from the result that M. acuminata tops the list of the well favoured chewing sticks. Other types of chewing sticks that rank high include fagara (Zanthophylum zanthoxonoides) and Ira (Rauwolfia vomitora). Bush meat is also cherished by people most especially in urban centres where it is regarded as a delicacy. Despite the preference of bush meat, the rate of consumption is still low relative to other animal protein sources. Apart from these two NTFPs, several others of economic, nutritional and medicinal importance exist. A list of some of them is made with their uses. NTFPs are grossly affected by seasonal changes and this in turns affect their availability and prices. In all, considering NTFPs in the light of economic gain alone will be parochial even though analysis for the marketing of the two NTFPs shows that they are viable business ventures. The values should extend beyond the economic gain to other values which are indispensable to the existence of man. A major but neglected aspect is the medicinal aspect of NTFPs.